2004
DOI: 10.2166/wst.2004.0344
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of brominated organic disinfection by-products to the mutagenicity of drinking water

Abstract: The activity inducing chromosomal aberrations of the mixture of brominated disinfection by-products (DBPs) was approximately three times higher than that of the chlorinated counterparts for the same hypohalous acid dose. With the combination of chromosomal aberration test and a new analytical technique to differentiate total organic chlorine (TOCl) and total organic bromine (TOBr), it was found that TOBr was correlated to the mutagenicity of chlorinated waters. It was also implied that for a bromide-to-TOC rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…It is likely that brominated HAAs were preferentially produced for the DOM after ozonation or GAC because bromination by HOBr (an intermediate species from the reaction of bromide and chlorine ions) occurs more rapidly than chlorination (e.g., Acero et al, 2005). As brominated compounds are known to more toxic than their chlorinated counterparts in general (Echigo et al, 2004) and among the HAAs (Plewa et al, 2002) regulations and monitoring focusing only on chlorinated HAAs may not be sufficient to guarantee the safety of finished water. Relative contributions of DOM fractions to HAA formation potential at each treatment stage (Relative contributions were calculated with the DOC percentages and HAA formation potentials.…”
Section: Haa Formation Characteristics From Different Dom Fractionsmentioning
confidence: 99%
“…It is likely that brominated HAAs were preferentially produced for the DOM after ozonation or GAC because bromination by HOBr (an intermediate species from the reaction of bromide and chlorine ions) occurs more rapidly than chlorination (e.g., Acero et al, 2005). As brominated compounds are known to more toxic than their chlorinated counterparts in general (Echigo et al, 2004) and among the HAAs (Plewa et al, 2002) regulations and monitoring focusing only on chlorinated HAAs may not be sufficient to guarantee the safety of finished water. Relative contributions of DOM fractions to HAA formation potential at each treatment stage (Relative contributions were calculated with the DOC percentages and HAA formation potentials.…”
Section: Haa Formation Characteristics From Different Dom Fractionsmentioning
confidence: 99%
“…Numerous studies have been conducted on the comparative toxicity of haloaliphatic DBPs in drinking water using different bioassay species, including bacteria, Chinese hamster ovary cells, and human cells. These studies have shown that iodo-DBPs were generally significantly more cytotoxic and genotoxic than their bromo-analogues, which in turn were more toxic than their chloro-analogues (Plewa et al, , 2008a(Plewa et al, , 2008bEchigo et al, 2004;Richardson et al, 2007;Richardson et al, 2008;Dad et al, 2013;Pals et al, 2013). Most recently, Yang and Zhang (2013) conducted toxicity tests for 24 halo-DBPs (most of which were newly identified in chlorinated saline wastewater effluents) using a marine polychaete Platynereis dumerilii, and found that this toxicity rank order (i.e., iodo-DBPs > bromoanalogues > chloro-analogues) applied also to the heterotrophic marine polychaete; moreover, the newly identified halophenolic DBPs were significantly more toxic than commonly known trihalomethanes and haloacetic acids, most of which have been regulated in the Disinfectants/DBPs rule by the U.S. EPA (2006).…”
Section: Introductionmentioning
confidence: 99%
“…During chlorination Br − is oxidized by free chlorine to bromine, which as a halogenation agent forms brominated DBPs including trihalomethanes (THMs) and haloacetic acids (HAAs). Several previous studies have shown the effects of Br − on formation of THMs and HAAs during chlorination (Pourmoghaddas et al, 1993;Rathbun, 1996;Gibbons and Laha, 1999;Clark et al, 2001;Richardson et al, 2003;Echigo et al, 2004;Lekkas and Nikolaou, 2004). The bromine incorporation factor was employed as a useful index to describe the distribution of four THM compounds when a natural water was chlorinated (Rathbun, 1996).…”
Section: Introductionmentioning
confidence: 99%